The Effect of Empowering Leadership and Corporate Culture on Change-Oriented Organizational Citizenship Behaviour Moderated by Self-Efficacy on Leadership Elements at PT Garuda Maintenance Facility Aeroasia Tbk, Line Maintenance Division - Wicaksono, Ritya Dimas; Asmony, Thatok; Nurmayanti, Siti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Empowering Leadership and Corporate Culture on Change-Oriented Organizational Citizenship Behavior (CO-OCB), with Self-Efficacy as a moderating variable among leaders at PT Garuda Maintenance Facility (GMF) AeroAsia Tbk, Line Maintenance Division. The phenomenon underlying this research is GMF’s need to enhance employees’ proactive and innovative behaviors in supporting organizational transformation, particularly in addressing the global challenges of the aviation industry. This research employs a quantitative approach using a survey method, with questionnaires distributed to leaders within the Line Maintenance Division of GMF. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The results reveal that Empowering Leadership has a significant positive effect on CO-OCB, and Corporate Culture also has a significant positive effect on CO-OCB. Furthermore, the moderating effect of Self-Efficacy was found to weaken the relationship between Empowering Leadership and CO-OCB, while conversely strengthening the relationship between Corporate Culture and CO-OCB. The findings of this study provide theoretical contributions to the development of human resource management and organizational behavior literature, as well as practical implications for GMF’s management in reinforcing leadership styles and work cultures that foster innovation and continuous organizational change in the workplace.